Exploring Negative Human Traits: A Thematic Tafsir of The Qur’an - Djuned, Muslim; Akbar, Khalis; Furqan, Furqan (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan Pusat Jurnal Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This article explores the intricate Qur’anic discourse on human nature, emphasizing the dualism of human existence and the potential for both moral elevation and descent. Employing thematic Tafsir, the study elucidates how the Qur’an portrays human beings as creatures of complex constitution—body, soul, and intellect—crafted in the most perfect form but susceptible to degradation to the lowest states. It further investigates negative human traits such as miserliness, impulsiveness, and injustice, providing a deep dive into traditional exegeses and contemporary interpretations. By analyzing these traits through the Qur’anic lens, the paper offers insights into the ethical and moral challenges humans face and the divine guidance provided to overcome these. Methodologically, the research synthesizes Qur’anic verses and scholarly interpretations, enriched by insights from Sufism and psychology, to construct a comprehensive understanding of human emotional and moral states. The findings suggest that awareness and self-reflection are crucial in mitigating negative traits and fostering a moral and spiritually aligned life.